2016
DOI: 10.1149/2.1211614jes
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Method Prepared La-Doped ZnWO4Nanospheres as Electrocatalytic Sensing Materials for Selective and Sensitive Determination of Dopamine and Uric Acid

Abstract: La-doped ZnWO 4 nanospheres were successfully synthesized by a hydrothermal synthesis method and further investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). A novel electrochemical sensor has been fabricated by carbon paste electrode (CPE) coated with the prepared La-doped ZnWO 4 nanospheres. Electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were applied to characterize the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Non-expensive and robust non-enzymatic sensors perform direct oxidation of UA on the surface of the electrode material [ 29 , 30 ]. Various materials, such as covalent organic and metal incorporated conductive polymers [ 13 , 16 , 19 , 23 ], metal oxides [ 30 , 31 , 32 ], carbon-based materials, and their composites [ 11 , 12 , 33 ], have been tested for UA detection [ 5 , 26 ]. These nanomaterials have been recognized as promising materials for the development of analytical methods for the detection not only of UA but also of numerous other biologically active compounds [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-expensive and robust non-enzymatic sensors perform direct oxidation of UA on the surface of the electrode material [ 29 , 30 ]. Various materials, such as covalent organic and metal incorporated conductive polymers [ 13 , 16 , 19 , 23 ], metal oxides [ 30 , 31 , 32 ], carbon-based materials, and their composites [ 11 , 12 , 33 ], have been tested for UA detection [ 5 , 26 ]. These nanomaterials have been recognized as promising materials for the development of analytical methods for the detection not only of UA but also of numerous other biologically active compounds [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of La [ 32 , 38 , 39 ]-based electrode materials has been reported in the literature with the main applications in fuel cells [ 40 , 41 , 42 ] and sensing devices [ 43 , 44 , 45 , 46 ], while Wang et al [ 47 ] used LaFeO 3 for the simultaneous determination of dopamine, uric acid and ascorbic acid, thus proving the materials’ compatibility with these analytes. La doping can affect lattice structures and phase transformations of compounds due to its larger atomic radius and unique electron structure, thus enhancing the catalytic and electrochemical properties of La-doped materials [ 32 ]. Furthermore, Guo et al [ 48 ] suggested that the alkaline properties of La(OH) 3 contribute to the acidic analytes’ bonding.…”
Section: Introductionmentioning
confidence: 99%